Effect of Teams Games Tournament Model with Interacty.me Media on Mathematics Learning Activeness Among Fifth-Grade Students - Azizah, Ratna Nur; Fikriyah, Fikriyah; Huda, Khozinul (Journal of Innovation and Research in Primary Education, 2025)
Student engagement in mathematics learning remains a persistent challenge in elementary education, with traditional teacher-centered approaches often resulting in passive learning environments and limited student participation. This study investigated the effect of integrating the Teams Games Tournament (TGT) cooperative learning model with Interacty.me digital media on fifth-grade students' mathematics learning engagement. A quasi-experimental design with non-equivalent control groups was employed at SD Negeri 1 Weru Lor, Indonesia. Fifty-five fifth-grade students were purposively selected and assigned to experimental (n=26) and control (n=29) groups. The experimental group received TGT instruction enhanced with Interacty.me digital platform, while the control group experienced conventional teaching methods. Learning engagement was measured using a validated 14-item questionnaire (α = 0.663) administered as pre-test and post-test. Data analysis utilized SPSS 27.0, including descriptive statistics, assumption testing, and Mann-Whitney U tests due to non-normal data distribution. Statistical analysis revealed significant differences between groups (p = 0.000), with the experimental group demonstrating superior post-test engagement scores (M = 41.27, SD = 6.03) compared to the control group (M = 37.45, SD = 5.89). Normalized gain analysis showed the experimental group achieved 12.25% improvement versus 8.82% in the control group, representing a 39% relative advantage in engagement enhancement. The findings confirm that technology-enhanced cooperative learning effectively addresses student disengagement by simultaneously targeting cognitive, behavioral, and affective engagement dimensions. The TGT-Interacty.me integration operationalized Self-Determination Theory principles through gamification elements, peer collaboration, and immediate feedback mechanisms. These results extend existing literature by demonstrating how digital platforms can enhance traditional cooperative learning approaches in elementary mathematics education.